2020
DOI: 10.1111/glob.12269
|View full text |Cite
|
Sign up to set email alerts
|

Elite professionals in transnational tax governance

Abstract: Since the global financial crisis, international corporate taxation has risen to the top of the global political agenda, as political leaders have called for collective action to shore up corporate tax systems. However, high‐level political initiative alone does not create new international corporate tax rules. Rather, these transnational governance processes are centrally driven by elite tax professionals competing for prestige and influence. In this article, I investigate this competition in the case of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…In this article, we examined how revolving doors informed the treatment of financial stability as an issue in international financial governance. We provided a conceptual basis for understanding linked ecologies and outlined how revolving doors can be located through a sequence analysis of careers and how such careers are embedded in networks (Christensen 2020). The linked ecologies framework provides a way of understanding how professional groups compete and cooperate, form alliances around hinges to permit consensus, and deploy avatars to persuade other professionals to treat issues in a different manner.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we examined how revolving doors informed the treatment of financial stability as an issue in international financial governance. We provided a conceptual basis for understanding linked ecologies and outlined how revolving doors can be located through a sequence analysis of careers and how such careers are embedded in networks (Christensen 2020). The linked ecologies framework provides a way of understanding how professional groups compete and cooperate, form alliances around hinges to permit consensus, and deploy avatars to persuade other professionals to treat issues in a different manner.…”
Section: Resultsmentioning
confidence: 99%
“…127 While it is essential to get the normative foundations right, politics and influence of elite tax professionals trump normative considerations in most interactions. 128 Ultimately there is a need for champions in governments and key international institutions on tax governancewhere the influence of human rights norms remains very limited. This article has suggested that if human rights are to have a say in the shaping of global tax rules, then there is an urgent need to bring the value-added of human rights norms, and the types of impact assessments the GPs push for, into the spaces where global tax governance is played out and to embed a defence of a rights-based order into the hard game of international political economy.…”
Section: Discussionmentioning
confidence: 99%
“…84 These companies, and their tax advisors, actively seek to take advantage of national differences in tax law, administrative/ enforcement capacity, political will and information in order to boost their own short-term returns. 85 While the nationality principle may have little cogence in international tax law, global companies based in the US or Europe, for example, respond very differently to their home states' strong tax administrations than to those of less powerful countries. 86 In sum, practical coherence over the implementation of the three principles discussed above is tempered strongly by asymmetries of effective power between States, which have resulted in a set of global tax arrangements biased against the weakest countries.…”
Section: A Economic Nexus and Its Discontentsmentioning
confidence: 99%
“…32 The link between legitimation (and legitimacy as such) and authority has been discussed extensively. For some recent links, see Christensen (2021) and Krisch (2017).…”
Section: Business Interests State Actors and Their Relationship In International Negotiationsmentioning
confidence: 99%